2022
DOI: 10.1101/2022.05.27.493720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Androgen Receptor is a Determinant of Melanoma targeted drug resistance

Abstract: Melanoma provides a primary benchmark for targeted drug therapy. Most melanomas with BRAFV600 mutations regress in response to BRAF/MEK inhibitors (BRAFi/MEKi). However, nearly all relapse within the first two years, and there is a connection between pathways involved in BRAFi/MEKi-resistance and poor response to immune checkpoint therapy. We recently showed that androgen receptor (AR) activity is required for melanoma cell proliferation and tumorigenesis. Here we find that AR expression is markedly increased … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…[30] Samarkina A investigation revealed a notable elevation in AR expression within BRAFi resistant melanoma cells, as well as in sensitive cells following brief exposure to BRAFi. [31] Feng L found that SERPINE1 exhibits high expression in gastric cancer, which is linked to an unfavorable prognosis. SERPINE1 may regulate the copper sag and immune microenvironment through a series of pathways.…”
Section: Discussionmentioning
confidence: 99%
“…[30] Samarkina A investigation revealed a notable elevation in AR expression within BRAFi resistant melanoma cells, as well as in sensitive cells following brief exposure to BRAFi. [31] Feng L found that SERPINE1 exhibits high expression in gastric cancer, which is linked to an unfavorable prognosis. SERPINE1 may regulate the copper sag and immune microenvironment through a series of pathways.…”
Section: Discussionmentioning
confidence: 99%